Multi- Objective Optimization of Shelling Process of an Engine - Operated Melon (Citrullus Laenatus Kuntze) Sheller - Yusuf, D. D.; Attanda, M. L.; Yusuf, H. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
The quest to develop an optimally operating mechanical device to shell melon seed (citrullus laenatus kuntze) has been a desirable objective over the past three decades. A melon sheller was constructed and optimized. The machine shelling performance analysis were based on shelling capacity, shelling efficiency, cleaning efficiency, seed loss, and damaged kernel. MATLAB 7.0, R2010a software was implemented using genetic algorithm technique for the optimization of the independent parameters and dependent response variables. A layout of the experiment was three speeds (S1, S2, S3), three feeding rate (P1, P2, P3) and three moisture contents (M1, M2, M3) which were arranged in a randomized complete design (3x3x3) in 3 replications. Melon (egusi) seed of Bara variety was used as test crop. Results showed that the machine shelling capacity and shelling efficiency increased with increase in the shelling drum speed, while the shelling capacity ranged between 20.07 and 44.90 kg/hr and the shelling efficiency ranged between 59.21 to 97.59 %. The optimum inputs were: moisture content (19.9 %), speed (1248 rpm), feed rate (42 kg/hr) at 4 passes and best performance parameters were: shelling efficiency (98.38 %), cleaning efficiency (48.79%), seed loss (8.74 %) and damaged kernel (10.44 %). The means of three replication of performance parameters were used in analysis. The shelling efficiency, cleaning efficiency, seed loss and damaged kernel were: 96.14, 49.15 %, 9.72 % and 10.52 % respectively, which is very close to the values (98.38 %, 48.79 %, 8.74 % and 10.44 %, respectively) obtained from the optimization process.